Self-assembly of hydrazide-linked porous organic polymers rich in titanium for efficient enrichment of glycopeptides and phosphopeptides from human serum - Wang, Danni; Feng, Quanshou; Luo, Yiting; Wang, Weimin; Yan, Yinghua; Ding, Chuan-Fan (Analyst (London), 2023)
In this work, titanium-rich hydrazide-linked porous organic polymers (hydrazide-POPs-Ti 4+ ) were synthesized using hydrazine, 2,3-dihydroxyterephthalaldehyde (DHTA) and trimethyl 1,3,5-benzenetricarboxylate (TP) as the ligands. Hydrazide-POPs-Ti 4+ combined with HILIC and IMAC can be used for simultaneous enrichment of glycopeptides and phosphopeptides. The detection limit of this protocol is 0.1 fmol μL −1 for glycopeptides and 0.005 fmol μL −1 for phosphopeptides, and the selectivities are 1 : 1000 and 1 : 2000 for glycopeptides and phosphopeptides, respectively. For practical bio-sample analysis, 201 glycopeptides associated with 129 glycoproteins and 26 phosphopeptides associated with 21 phosphoproteins were selectively captured from healthy human serum, and 186 glycopeptides associated with 117 glycoproteins and 60 phosphopeptides associated with 50 phosphoproteins were enriched in the serum of breast cancer patients. Gene Ontology analysis indicated that the identified glycoproteins and phosphoproteins were linked to breast cancer, including the binding of complement component C1q and low-density lipoprotein particles, protein oxidation and complement activation, suggesting that these connected pathways are probably engaged in the disease pathology of breast cancer. The mechanism of selective enrichment by hydrazide-POPs-Ti 4+ .